2017
DOI: 10.1177/0146167217736048
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Thinking as a Conflict-Resolution Intervention: Comparison to Alternative Interventions and Examination of Psychological Mechanisms

Abstract: Conflict-resolution interventions based on the paradoxical thinking principles, that is, expressing amplified, exaggerated, or even absurd ideas that are congruent with the held conflict-supporting societal beliefs, have been shown to be an effective avenue of intervention, especially among individuals who are adamant in their views. However, the question as to why these interventions have been effective has remained unanswered. In the present research, we have examined possible underlying psychological mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
68
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 26 publications
3
68
2
Order By: Relevance
“…This article proposes a new and alternative approach to these interventions based on the principles of paradoxical thinking (Hameiri, Nabet, Bar‐Tal, & Halperin, ; Hameiri, Porat, Bar‐Tal, Bieler, & Halperin, ; Hameiri, Porat, Bar‐Tal, & Halperin, ; Swann, Pelham, & Chidester, ). In our research, conducted in the context of an intractable conflict, the conventional approaches to attitude change were found to be less effective, especially with individuals who are more adamant in their opposition to peaceful conflict resolution.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This article proposes a new and alternative approach to these interventions based on the principles of paradoxical thinking (Hameiri, Nabet, Bar‐Tal, & Halperin, ; Hameiri, Porat, Bar‐Tal, Bieler, & Halperin, ; Hameiri, Porat, Bar‐Tal, & Halperin, ; Swann, Pelham, & Chidester, ). In our research, conducted in the context of an intractable conflict, the conventional approaches to attitude change were found to be less effective, especially with individuals who are more adamant in their opposition to peaceful conflict resolution.…”
mentioning
confidence: 99%
“…In our research, conducted in the context of an intractable conflict, the conventional approaches to attitude change were found to be less effective, especially with individuals who are more adamant in their opposition to peaceful conflict resolution. We examined whether an unconventional approach might be more useful in these cases (Hameiri et al., , , ). Paradoxical thinking interventions do not directly contradict the positions of these individuals as the conventional approaches do.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To address that challenge, Swann, and colleagues (Swann, Pelham, & Chidester, ) suggested that using messages which are consistent with an individual's view, but are formulated in an amplified, exaggerated, or even absurd manner, would ultimately lead to the unfreezing and reevaluation of held attitudes. A long series of lab and field studies then showed that such exposure to paradoxical messages can improve intergroup attitudes and lead people to increased support for political intergroup compromises (Hameiri, Porat, et al, ; Hameiri, Bar‐Tal, & Halperin, ; Hameiri, Nabet, Bar‐Tal, & Halperin, ). What content is embedded within paradoxical thinking interventions and to what extent is it congruent or incongruent with the content of certain ideological views?…”
Section: Interventions Based On New Experiences: Paradoxical Thinkingmentioning
confidence: 99%